2009
DOI: 10.1037/a0015421
|View full text |Cite
|
Sign up to set email alerts
|

Monetary incentives improve recall of research consent information: It pays to remember.

Abstract: Research participants often fail to recall substantial amounts of informed consent information after delays of only a few days. Numerous interventions have proven effective at improving consent recall; however, virtually all have focused on compensating for potential cognitive deficits and have ignored motivational factors. In this pilot study, we randomly assigned 31 drug court clients participating in a clinical research trial to a standard consent procedure or to the same procedure plus incentives for corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…Similar to our prior studies (Festinger et al, 2005, 2009) examining the use of cash remuneration to substance abusing research participants, these data provide additional support for the safety of cash payments. This is particularly important given the potential reductions in staff burden and associated costs (e.g., voucher printing, stocking of prize cabinets, inventory counts) that could be realized in a cash-based CM procedure.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Similar to our prior studies (Festinger et al, 2005, 2009) examining the use of cash remuneration to substance abusing research participants, these data provide additional support for the safety of cash payments. This is particularly important given the potential reductions in staff burden and associated costs (e.g., voucher printing, stocking of prize cabinets, inventory counts) that could be realized in a cash-based CM procedure.…”
Section: Discussionsupporting
confidence: 80%
“…The Recent Behavior Scale (RBS; Festinger, et al, 2005; 2009) is an 8-item, self-report assessment that inquires about the number of days participants engaged in drug and alcohol use and other high-risk behavior (i.e., gambling and solicitation) in the past 30 days. These behaviors were selected for inclusion based on expert consensus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that cash payments did not have a significant impact on participants' drug use or their perceptions of the coerciveness of the research, although higher cash amounts did improve study retention. Moreover, in a related study conducted by Festinger et al (2009), they found that payments were associated with higher comprehension (and retention) of consent forms.…”
Section: Discussion and Summarymentioning
confidence: 94%
“…Participants are often unaware that they were participating in a research study, fail to recall study-related risks, are unable to describe randomization procedures or placebo interventions, and are unaware that they can withdraw from a study without negative consequences. 35 Research in a population of substance abusing offenders 6,7 revealed that participants failed to recall 60% of consent information just two weeks after their initial consent, calling into question whether participants can make informed decisions about their initial or continued involvement in research.…”
mentioning
confidence: 99%